From Classical Repertoire to Piano Accompaniment: Development of a Learning Model Based on the needs of the Music Industry - Yogha Pratama, Olan; Sabetra, Firnando; Dilfa, Alrizka Hairi; Yusman, Ahmad Fauzan; sari, Ayuthia Mayang (Insan Akademika Publications, 2025)
Formal music education in college, especially for piano majors, has emphasized classical repertoire and profound solo playing techniques. However, previous graduate evaluations show that many have difficulty adjusting to the demands of the popular music industry, which demands more flexibility in piano accompaniment, improvisation, and harmony. This research aims to practice the piano accompaniment learning model in grade 3 of the current major. Action research is the methodology used, and a descriptive qualitative approach is needed using document analysis, observation, and interviews. The findings of this study are expected to help music education institutions better understand their students’ business demands and professional requirements after graduation.